High-performance composite material for micro-drill shank and preparation method thereof
Patent Information
- Application Number
- CN202611048361.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-16
AI Technical Summary
总体而言,现有金属材料体系在同时兼顾高硬度、高抗拉强度、高弹性模量与耐腐蚀等多维度性能需求方面存在固有的局限性
(3)对毛坯进行深冷处理,得到中间坯体;
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of micro drill holders, and more specifically, to high-performance composite materials for micro drill holders and their preparation methods. Background Technology
[0002] Micro drills (or simply micro drills) are precision machining tools with a diameter of less than 0.2 mm. They are widely used in the electronics manufacturing industry, especially in the machining of micro-holes in printed circuit boards (PCBs), where stringent precision requirements apply. In recent years, with the continuous advancement of electronic information and communication technologies, the practical diameter of micro drills has gradually decreased to 0.05 mm or even smaller, leading to further increases in the requirements for various performance indicators of micro drills.
[0003] The drill bit portion of a micro drill is typically made of cemented carbide to achieve excellent hardness (wear resistance), tensile strength (fracture resistance), and elastic modulus (stiffness). However, cemented carbide is expensive and brittle, making it prone to chipping under clamping stress. Therefore, in practical applications, the cemented carbide drill bit is often welded to the tool holder. The tool holder, as the clamping and force-transmitting component of the micro drill, also needs to meet the aforementioned performance requirements. Specifically, during frequent clamping operations, the tool holder and collet repeatedly come into contact and rub against each other, requiring the tool holder surface to have good hardness to maintain clamping accuracy. Micro drills typically operate at extremely high speeds, requiring the tool holder material to have high tensile strength to reduce centrifugal loads and the risk of dynamic instability during high-speed rotation. During drilling, the cutting part of the micro drill is prone to bending and wobbling due to the cutting forces, requiring the tool holder to have sufficient elastic modulus to suppress vibration and maintain machining accuracy. In addition, the machining environment widely uses cutting fluids and contains humid and hot atmospheres, requiring the tool holder material to have excellent corrosion resistance to prevent the accumulation of surface corrosion products from adversely affecting the accuracy and reliability of the clamping surface. In summary, micro drill tool holder materials must simultaneously possess comprehensive properties such as high hardness, high tensile strength, high elastic modulus, and excellent corrosion resistance.
[0004] Currently, micro drill shanks are mainly made of alloy steel and stainless steel. Alloy steel boasts excellent overall mechanical properties, but its corrosion resistance is relatively insufficient. In wet machining environments, its surface condition is prone to deterioration after prolonged use, affecting the stability of the clamping fit. Stainless steel offers superior corrosion resistance, but its hardness still needs improvement. Furthermore, its rigidity is insufficient due to limitations in its elastic modulus. Overall, existing metal material systems have inherent limitations in simultaneously meeting the multi-dimensional performance requirements of high hardness, high tensile strength, high elastic modulus, and corrosion resistance. Summary of the Invention
[0005] The technical problem to be solved by this invention is to provide a high-performance composite material for micro-drill shanks that has good corrosion resistance while maintaining or even enhancing the material's hardness, tensile strength, and elastic modulus, and a method for preparing the same. The technical solution is as follows: High-performance composite material for micro drill holders, comprising the following parts by weight of raw materials: 45–85 parts of elemental iron powder; 5 to 45 parts of hard phase, including titanium carbonitride powder; 8 to 12 parts of nickel-based powder, including elemental nickel powder and nickel alloy powder.
[0006] The advantages of the high-performance composite material for micro-drill tool holders of the present invention are: (1) Titanium carbonitride, as a hard reinforcing phase, has an elastic modulus much higher than that of the iron matrix. After being dispersed in the iron matrix, it can effectively improve the overall elastic modulus of the composite material, suppress the bending and swaying caused by the cutting force during high-speed rotating drilling of the micro-drill, thereby maintaining the machining accuracy; at the same time, titanium carbonitride itself has extremely high hardness, which can significantly improve the wear resistance of the tool holder surface during frequent clamping contact with the collet, and maintain the long-term stability of the dimensional accuracy of the clamping surface. (2) The introduction of nickel-based powder is beneficial to stabilizing the structure of the iron matrix and improving its tensile strength. Nickel element dissolved in the iron matrix can play a solid solution strengthening role, which is beneficial to improving the strength and toughness of the matrix, ensuring that the tool holder does not undergo brittle fracture under complex load conditions such as high-speed rotation and frequent clamping; nickel element is also beneficial to improving the compatibility between the iron matrix and titanium carbonitride particles, thereby improving the overall mechanical properties of the composite material. (3) There is a synergistic effect among the components: the iron matrix provides tensile strength support and load transfer skeleton for the titanium carbonitride particles, the titanium carbonitride particles constrain the deformation of the matrix and bear the main wear load, and the nickel element optimizes the intrinsic properties of the matrix and the quality of interfacial bonding. The three components work together within the ratio range to achieve comprehensive optimization of the composite material in terms of hardness, tensile strength, elastic modulus and wear resistance, overcoming the inherent limitations of existing single metal system materials.
[0007] As a further improvement to the aforementioned high-performance composite material for micro-drill tool holders: the nickel alloy powder includes nickel-chromium powder and nickel-aluminum powder, with a weight ratio of nickel elemental powder, nickel-chromium powder, and nickel-aluminum powder of (1.5–5):(1.5–4):1. Chromium, after being dissolved in the iron matrix, helps improve the corrosion resistance of the composite material, effectively preventing the erosion of the tool holder surface by cutting fluid and humid environments, avoiding the deterioration of clamping accuracy caused by the accumulation of corrosion products, and also helps to further improve the hardness of the iron matrix; aluminum helps improve the tensile strength and creep resistance of the material; the synergistic control of the proportions of the three nickel-based powders achieves a good balance between corrosion resistance, mechanical strengthening, and matrix properties.
[0008] As a further improvement to the aforementioned high-performance composite material for micro-drill shanks, it further includes 1 to 8 parts of aluminum-containing MAX phase powder, wherein the aluminum-containing MAX phase powder is at least one of Ti2AlC and Ti3AlC2, and the particle size of the aluminum-containing MAX phase powder is 0.5 to 5 μm. Thus, the aluminum-containing MAX phase possesses a unique nano-layered crystal structure, which is beneficial for participating in the strengthening of the matrix during sintering, thereby improving the tensile strength of the composite material. Compared to directly adding aluminum powder, using the aluminum-containing MAX phase is more conducive to the uniform distribution of elements, resulting in a better strengthening effect. Simultaneously, the aluminum-containing MAX phase is beneficial for supplementing the content of hard reinforcing phases, increasing the material's hardness. Its unique layered structure also helps improve the damage tolerance and fracture toughness of the composite material. Furthermore, the aluminum-containing MAX phase helps alleviate the thermal mismatch between titanium carbonitride and the iron matrix, reducing the risk of microcrack initiation at the interface.
[0009] As a further improvement to the aforementioned high-performance composite material for micro-drill shanks, it also includes 1 to 3 parts of molybdenum carbide powder, wherein the particle size of the molybdenum carbide powder is 0.5 to 2 μm. Thus, molybdenum carbide is beneficial for improving the bonding quality between the reinforcing phase and the matrix, enhancing interfacial bonding strength and load transfer efficiency.
[0010] As a further improvement to the aforementioned high-performance composite material for micro-drill shanks: the particle size of the iron powder is 0.5–2 μm; the particle size of the hard phase is 0.3–3 μm; and the particle size of the nickel-based powder is 0.5–4 μm. This ensures uniform powder mixing and sintering activity, facilitating the acquisition of a composite material with a fine and uniform microstructure, high density, and excellent mechanical properties.
[0011] The above-mentioned method for preparing high-performance composite materials for micro-drill shanks includes the following steps: (1) Add each raw material to a ball mill according to the proportion, add a molding agent and mix by ball milling, then dry and granulate and press to form a compact. (2) The pressed blank is sintered to obtain a blank; (3) The blank is subjected to deep cryogenic treatment to obtain an intermediate blank; (4) The intermediate billet is subjected to aging treatment to obtain the finished billet; (5) Grinding the blank to obtain a high-performance composite material for micro drill holder.
[0012] The advantages of the preparation method of the high-performance composite material for micro-drill holders of the present invention are: (1) Cryogenic treatment is beneficial to promoting the transformation of the unstable residual structure in the iron matrix after sintering and cooling, and improving the hardness and dimensional stability of the material; cryogenic treatment is also beneficial to relieving the residual stress of sintering and improving the dimensional stability and fatigue life of the micro-drill holder during high-speed rotation. (2) Aging treatment is beneficial to forming a strengthening phase and improving the strength of the material; at the same time, appropriate aging can eliminate the internal stress introduced by cryogenic treatment, so that the strength and tensile strength of the material can reach the best balance. (3) Sintering provides a suitable precursor structure for cryogenic treatment, cryogenic treatment provides favorable microstructure conditions for aging, and aging completes the final fine control of microstructure on the basis of the first two steps. The three steps work together to achieve comprehensive optimization of the hardness, tensile strength and dimensional stability of the composite material.
[0013] As a further improvement to the above preparation method: In step (1), the molding agent includes paraffin wax and polyethylene glycol, and the weight ratio of the raw material mixed powder to paraffin wax and polyethylene glycol is 100:(1.5~3):(1.5~3); the ball milling uses cemented carbide grinding balls, the ball-to-material mass ratio is (6~8):1, the ball milling speed is 150~300 r / min, and the ball milling time is 24~72 hours; the pressing pressure is 350~500 MPa. This helps to fully disperse the powder, resulting in a moderate compaction density, providing good precursor conditions for uniform densification and interfacial reactions during sintering.
[0014] As a further improvement to the above preparation method: the sintering treatment in step (2) is as follows: Under an argon atmosphere and normal pressure, the temperature is raised from room temperature to 300–550°C and held for 2–6 hours. Under vacuum conditions, continue heating to 1100–1200℃ and hold for 0.5–1 hour, then heat to 1280–1320℃ and hold for 0.5–1 hour. Argon gas is introduced to 5-10 MPa, and the temperature is raised to 1350-1410℃ and held for 0.5-1.5 hours. The blank is then cooled in the furnace.
[0015] Therefore, the multi-stage gradient sintering process can precisely control the formation sequence of matrix alloying, interfacial reaction and densification, avoid the inhomogeneity of the microstructure caused by the competition of various reactions, and obtain composite materials with uniform phase distribution and excellent interfacial bonding.
[0016] As a further improvement to the above preparation method: in step (3), the cryogenic treatment involves immersing the blank in liquid nitrogen for 2 to 6 hours, then taking it out and allowing it to naturally return to room temperature, repeating the cryogenic treatment 1 to 3 times. This helps to further transform the retained austenite and form the precipitated phase, while avoiding microcracks caused by excessive thermal shock, thus ensuring the dimensional stability and fatigue performance of the material.
[0017] As a further improvement to the above preparation method: the aging treatment in step (4) involves heating the intermediate preform from room temperature to 500-700°C under an argon atmosphere and normal pressure, holding it at that temperature for 2-5 hours, and then cooling it in the furnace. This helps to control the size and distribution density of the precipitated strengthening phase, thereby maximizing the strengthening effect of precipitation while eliminating the internal stress introduced by the previous process.
[0018] The present invention will be further described below through specific embodiments. Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Detailed Implementation
[0019] The present invention will now be clearly and completely described. Those skilled in the art will be able to implement the present invention based on this description. Before describing the present invention, it should be particularly noted that: The technical solutions and features provided in the various parts of this invention, including the following description, can be combined with each other without conflict.
[0020] Furthermore, the embodiments of the present invention described below are generally only some, not all, of the embodiments of the present invention. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention.
[0021] Regarding the terminology and units used in this invention: The terms "comprising," "having," and any variations thereof in the specification, claims, and related parts of this invention are intended to cover non-exclusive inclusion.
[0022] Example 1
[0023] The high-performance composite material for micro-drill shanks and its preparation method in this embodiment are as follows: (1) Add each raw material to a ball mill according to the proportion, add a molding agent and mix by ball milling, then dry and granulate and press to form a compact. The raw materials include 70 parts by weight of elemental iron powder, 20 parts by weight of titanium carbonitride powder, and 10 parts by weight of nickel-based powder; the particle size of the elemental iron powder is 0.5-2 μm; the particle size of the titanium carbonitride powder is 0.3-3 μm; the nickel-based powder includes elemental nickel powder, nickel-chromium powder, and nickel-aluminum powder, with a weight ratio of 2.5:1.5:1 and a particle size of 0.5-4 μm. The molding agent includes paraffin wax and polyethylene glycol. The weight ratio of the raw material mixed powder to paraffin wax and polyethylene glycol is 100:2:2. The ball milling uses cemented carbide grinding balls with a ball-to-material mass ratio of 8:1, a ball milling speed of 200 r / min, and a ball milling time of 48 hours. After drying and granulation, the powder is pressed into shape in an isostatic press under a pressure of 450 MPa to obtain the pressed compact.
[0024] (2) The pressed blank is sintered to obtain a blank; The sintering process is as follows: under an argon atmosphere and normal pressure, the temperature is raised from room temperature to 450°C and held for 4 hours; under vacuum conditions, the temperature is further raised to 1380°C and then argon gas is introduced to 8MPa, and then held for 1 hour. The blank is obtained by cooling with the furnace.
[0025] (3) The blank is subjected to deep cryogenic treatment to obtain an intermediate blank; Cryogenic treatment involves immersing the blank in liquid nitrogen for 4 hours, then allowing it to naturally return to room temperature. This process is repeated once.
[0026] (4) The intermediate billet is subjected to aging treatment to obtain the finished billet; The aging process involves heating the intermediate billet from room temperature to 600°C under an argon atmosphere and normal pressure, holding it at that temperature for 3 hours, and then cooling it in the furnace.
[0027] (5) Grinding the blank to obtain a high-performance composite material for micro drill holder.
[0028] Tests showed that the high-performance composite material of this embodiment has a hardness of 56 HRC, an elastic modulus of 252 GPa, a tensile strength of 1210 MPa, an elongation of 11.9%, and no wear marks were observed after 100 repeated clamping cycles. No corrosion marks were observed in a simulated service environment containing cutting fluid.
[0029] Example 2
[0030] Compared with Example 1, the difference between the high-performance composite material for micro drill holders and its preparation method in this example is that the raw materials include 85 parts by weight of elemental iron powder, 5 parts by weight of titanium carbonitride powder, and 10 parts by weight of nickel-based powder.
[0031] Tests showed that the high-performance composite material of this embodiment has a hardness of 49 HRC, an elastic modulus of 221 GPa, a tensile strength of 1170 MPa, an elongation of 13.3%, and no obvious wear marks were observed after 100 repeated clamping cycles. No corrosion marks were observed in a simulated service environment containing cutting fluid.
[0032] Example 3
[0033] Compared with Example 1, the difference between the high-performance composite material for micro drill holders and its preparation method in this example is that the raw materials include 45 parts by weight of elemental iron powder, 45 parts by weight of titanium carbonitride powder, and 10 parts by weight of nickel-based powder.
[0034] Tests showed that the high-performance composite material of this embodiment has a hardness of 60 HRC, an elastic modulus of 309 GPa, a tensile strength of 1130 MPa, and an elongation of 6.2%. No corrosion was observed in a simulated service environment containing cutting fluid.
[0035] Example 4
[0036] Compared with Example 1, the difference between the high-performance composite material for micro-drill shanks and its preparation method in this example is that the weight ratio of nickel elemental powder, nickel-chromium powder and nickel-aluminum powder in the nickel-based powder is 1.5:2.5:1.
[0037] Tests showed that the high-performance composite material of this embodiment has a hardness of 55 HRC, an elastic modulus of 250 GPa, a tensile strength of 1260 MPa, and an elongation of 10.2%. No corrosion was observed in a simulated service environment containing cutting fluid.
[0038] Example 5
[0039] Compared with Example 1, the difference between the high-performance composite material for micro-drill shanks and its preparation method in this example is that the weight ratio of nickel elemental powder, nickel-chromium powder and nickel-aluminum powder in the nickel-based powder is 5:4:1.
[0040] Tests showed that the high-performance composite material of this embodiment has a hardness of 55 HRC, an elastic modulus of 251 GPa, a tensile strength of 1230 MPa, and an elongation of 10.8%. No corrosion was observed in a simulated service environment containing cutting fluid.
[0041] Example 6
[0042] Compared with Example 1, the difference between the high-performance composite material for micro-drill holders and its preparation method in this example is as follows: the sintering treatment is as follows: under argon atmosphere and normal pressure, the temperature is raised from room temperature to 450°C and held for 4 hours; under vacuum conditions, the temperature is further raised to 1100°C and held for 0.5 hours, then raised to 1280°C and held for 1 hour; argon gas is introduced to 8MPa, and the temperature is further raised to 1380°C and held for 1 hour, and then cooled with the furnace to obtain the blank.
[0043] Tests showed that the high-performance composite material of this embodiment has a hardness of 56 HRC, an elastic modulus of 256 GPa, a tensile strength of 1270 MPa, and an elongation of 11.1%. No corrosion was observed in a simulated service environment containing cutting fluid.
[0044] Example 7
[0045] Compared with Example 1, the difference between the high-performance composite material for micro-drill shanks and its preparation method in this example is as follows: the sintering treatment is as follows: under argon atmosphere and normal pressure, the temperature is raised from room temperature to 450°C and held for 4 hours; under vacuum conditions, the temperature is further raised to 1200°C and held for 1 hour, then raised to 1320°C and held for 0.5 hours; argon gas is introduced to 8MPa, and the temperature is further raised to 1380°C and held for 1 hour, and then cooled with the furnace to obtain the blank.
[0046] Tests showed that the high-performance composite material of this embodiment has a hardness of 57 HRC, an elastic modulus of 258 GPa, a tensile strength of 1300 MPa, and an elongation of 10.6%. No corrosion was observed in a simulated service environment containing cutting fluid.
[0047] Example 8
[0048] Compared with Example 1, the difference between the high-performance composite material for micro drill holders and its preparation method in this example is that the raw materials include 70 parts by weight of elemental iron powder, 18 parts of titanium carbonitride powder, 10 parts of nickel-based powder, and 2 parts of molybdenum carbide powder, with the molybdenum carbide powder having a particle size of 0.5 to 2 μm.
[0049] Tests showed that the high-performance composite material of this embodiment has a hardness of 58 HRC, an elastic modulus of 255 GPa, a tensile strength of 1350 MPa, and an elongation of 9.5%. No corrosion was observed in a simulated service environment containing cutting fluid.
[0050] Example 9
[0051] Compared with Example 1, the difference between the high-performance composite material for micro drill holders and its preparation method in this example is that the raw materials include 65 parts by weight of elemental iron powder, 20 parts by weight of titanium carbonitride powder, 10 parts by weight of nickel-based powder, and 5 parts by weight of Ti2AlC powder, with the particle size of Ti2AlC powder being 0.5 to 5 μm.
[0052] Tests showed that the high-performance composite material of this embodiment has a hardness of 57 HRC, an elastic modulus of 261 GPa, a tensile strength of 1320 MPa, and an elongation of 8.5%. No corrosion was observed in a simulated service environment containing cutting fluid.
[0053] Example 10
[0054] Compared with Example 1, the difference between the high-performance composite material for micro drill holders and its preparation method in this example is that the raw materials include 65 parts by weight of elemental iron powder, 20 parts of titanium carbonitride powder, 10 parts of nickel-based powder, and 5 parts of Ti3AlC2 powder, with the particle size of Ti3AlC2 powder being 0.5 to 5 μm.
[0055] Tests showed that the high-performance composite material of this embodiment has a hardness of 58 HRC, an elastic modulus of 263 GPa, a tensile strength of 1370 MPa, and an elongation of 8.8%. No corrosion was observed in a simulated service environment containing cutting fluid.
[0056] Example 11
[0057] Compared with Example 1, the difference between the high-performance composite material for micro-drill holders and its preparation method in this example is that the cryogenic treatment involves immersing the blank in liquid nitrogen for 4 hours, then taking it out and allowing it to naturally return to room temperature, and performing the cryogenic treatment 3 times.
[0058] Tests showed that the high-performance composite material of this embodiment has a hardness of 58 HRC, an elastic modulus of 254 GPa, a tensile strength of 1330 MPa, and an elongation of 8.6%. No corrosion was observed in a simulated service environment containing cutting fluid.
[0059] Example 12
[0060] Compared with Example 1, the difference between the high-performance composite material for micro-drill shanks and its preparation method in this example is as follows: the raw materials include 65 parts by weight of elemental iron powder, 18 parts by weight of titanium carbonitride powder, 10 parts by weight of nickel-based powder, 5 parts by weight of Ti3AlC2 (particle size 0.5-5μm), and 2 parts by weight of molybdenum carbide powder (particle size 0.5-2μm); the material undergoes two cryogenic treatments; the sintering process is as follows: under an argon atmosphere and normal pressure, the temperature is raised from room temperature to 450°C and held for 4 hours; under vacuum conditions, the temperature is further raised to 1200°C and held for 1 hour, then raised to 1320°C and held for 0.5 hours; argon gas is introduced to 8MPa, and the temperature is further raised to 1380°C and held for 1 hour, followed by furnace cooling to obtain the blank.
[0061] Tests showed that the high-performance composite material of this embodiment has a hardness of 61 HRC, an elastic modulus of 271 GPa, a tensile strength of 1450 MPa, an elongation of 7.5%, and no wear marks were observed after 100 repeated clamping cycles. No corrosion marks were observed in a simulated service environment containing cutting fluid.
[0062] Compare with Example 1 Compared with Example 1, the difference between the high-performance composite material for micro-drill shanks and its preparation method in this comparative example is that the nickel-based powder consists entirely of 10 parts of elemental nickel powder, without nickel-chromium powder or nickel-aluminum powder.
[0063] Tests showed that the high-performance composite material of this comparative example had a hardness of 49 HRC, an elastic modulus of 249 GPa, a tensile strength of 1020 MPa, an elongation of 9.8%, wear marks were visible after 100 repeated clamping cycles, and slight corrosion marks were visible in a simulated service environment containing cutting fluid.
[0064] Compare with Example 2 Compared with Example 1, the difference between the high-performance composite material for micro-drill holders and its preparation method in this comparative example is that no cryogenic treatment is performed, that is, the blank is directly subjected to aging treatment after sintering.
[0065] Tests showed that the high-performance composite material of this control example had a hardness of 51 HRC, an elastic modulus of 248 GPa, a tensile strength of 1120 MPa, an elongation of 9.2%, and no obvious wear marks were observed after 100 repeated clamping cycles. No corrosion marks were observed in the simulated service environment containing cutting fluid.
[0066] Compare with Example 3 Compared with Example 1, the difference between the high-performance composite material for micro-drill holders and its preparation method in this comparative example is that no aging treatment is performed, that is, the intermediate blank is obtained by cryogenic treatment and then directly ground.
[0067] Tests showed that the high-performance composite material of this control example had a hardness of 53 HRC, an elastic modulus of 251 GPa, a tensile strength of 1100 MPa, an elongation of 5.8%, and no obvious wear marks were observed after 100 repeated clamping cycles. No corrosion marks were observed in the simulated service environment containing cutting fluid.
[0068] Compare with Example 4 Compared with Example 1, the difference between the high-performance composite material for micro-drill holders and its preparation method in this comparative example is that it does not undergo cryogenic treatment and aging treatment, that is, it is directly ground after sintering to obtain a blank.
[0069] Tests showed that the high-performance composite material of this control example had a hardness of 48 HRC, an elastic modulus of 245 GPa, a tensile strength of 1030 MPa, an elongation of 8.5%, and wear marks were visible after 100 repeated clamping cycles. No obvious corrosion was observed in a simulated service environment containing cutting fluid.
[0070] Comparing Example 1 with Comparative Examples 2, 3, and 4, it can be seen that cryogenic treatment increased the hardness (HRC) of Comparative Example 4 (48 HRC) to that of Comparative Example 3 (53 HRC), indicating that cryogenic treatment alone may promote the transformation of retained austenite into martensite. However, the untempered martensite exhibits high internal stress and brittleness, resulting in a decrease in elongation to 5.8%. Aging treatment increased the hardness (HRC / 1030 MPa) of Comparative Example 4 (48 HRC / 1030 MPa) to that of Comparative Example 2 (51 HRC / 1120 MPa), indicating that aging treatment may moderately improve hardness and strength and slightly improve plasticity through precipitation strengthening and residual stress elimination. When cryogenic treatment and aging treatment work synergistically, the martensite formed by cryogenic treatment is transformed into uniform tempered martensite after aging and tempering, and fine strengthening phases precipitate. This achieves both high hardness and high strength, while the elongation significantly increases to 11.9%, realizing the optimal balance between strength and toughness.
[0071] In the above performance tests: Hardness was tested in accordance with GB / T 230.1-2018 "Metallic materials Rockwell hardness test - Part 1: Test method".
[0072] The elastic modulus was tested in accordance with GB / T 38897-2020 "Ultrasonic Measurement Method for Elastic Modulus and Poisson's Ratio in Nondestructive Testing".
[0073] Tensile strength and elongation were tested in accordance with GB / T 228.1-2021 "Metallic materials - Tensile testing - Part 1: Test method at room temperature".
[0074] Wear test: The micro-drill shank sample was loaded into the spring collet of a PCB CNC drilling machine (Hitachi-H-MARK-30D), clamped with the spindle's rated clamping force, held for several seconds, and then released and removed. This was counted as one clamping cycle. After repeating the operation 100 times, the surface morphology of the clamping surface was observed under an optical microscope to determine whether there were visible scratches, grooves, or material peeling.
[0075] Corrosion test: The micro drill shank sample was immersed in water-soluble cutting fluid and continuously soaked at 40±2℃ for 120 hours. After cleaning and drying, the surface was observed visually and under an optical microscope for rust spots, pitting or discoloration.
[0076] The foregoing has described the relevant content of the present invention. Those skilled in the art will be able to implement the present invention based on these descriptions. All other embodiments obtained by those skilled in the art based on the above description of the present invention without inventive effort should fall within the scope of protection of the present invention.
Claims
1. A high-performance composite material for micro drill holders, characterized in that: The ingredients include the following parts by weight: 45–85 parts of elemental iron powder; 5 to 45 parts of hard phase, including titanium carbonitride powder; 8 to 12 parts of nickel-based powder, including elemental nickel powder and nickel alloy powder.
2. The high-performance composite material for micro-drill shanks according to claim 1, characterized in that: The nickel alloy powder includes nickel-chromium powder and nickel-aluminum powder, and the weight ratio of elemental nickel powder, nickel-chromium powder and nickel-aluminum powder is (1.5-5):(1.5-4):
1.
3. The high-performance composite material for micro-drill shanks according to claim 1, characterized in that: It also includes 1 to 8 parts of aluminum-containing MAX phase powder, wherein the aluminum-containing MAX phase powder is at least one of Ti2AlC and Ti3AlC2, and the particle size of the aluminum-containing MAX phase powder is 0.5 to 5 μm.
4. The high-performance composite material for micro-drill shanks according to claim 1, characterized in that: It also includes 1 to 3 parts of molybdenum carbide powder, wherein the particle size of the molybdenum carbide powder is 0.5 to 2 μm.
5. The high-performance composite material for micro-drill shanks according to any one of claims 1 to 4, characterized in that: The iron elemental powder has a particle size of 0.5–2 μm; the hard phase has a particle size of 0.3–3 μm; and the nickel-based powder has a particle size of 0.5–4 μm.
6. The method for preparing the high-performance composite material for micro-drill shanks according to any one of claims 1 to 5, characterized in that, Includes the following steps: (1) Add each raw material to a ball mill according to the proportion, add a molding agent and mix by ball milling, then dry and granulate and press to form a compact. (2) The pressed blank is sintered to obtain a blank; (3) The blank is subjected to deep cryogenic treatment to obtain an intermediate blank; (4) The intermediate billet is subjected to aging treatment to obtain the finished billet; (5) Grinding the blank to obtain a high-performance composite material for micro drill holder.
7. The preparation method according to claim 6, characterized in that: In step (1), the molding agent includes paraffin wax and polyethylene glycol, and the weight ratio of the raw material mixed powder to paraffin wax and polyethylene glycol is 100:(1.5~3):(1.5~3); the ball milling uses cemented carbide grinding balls, the ball-to-material mass ratio is (6~8):1, the ball milling speed is 150~300r / min, and the ball milling time is 24~72 hours; the pressing pressure is 350~500MPa.
8. The preparation method according to claim 6, characterized in that: The sintering process in step (2) is as follows: Under an argon atmosphere and normal pressure, the temperature is raised from room temperature to 300–550°C and held for 2–6 hours. Under vacuum conditions, continue heating to 1100–1200℃ and hold for 0.5–1 hour, then heat to 1280–1320℃ and hold for 0.5–1 hour. Argon gas is introduced to 5-10 MPa, and the temperature is raised to 1350-1410℃ and held for 0.5-1.5 hours. The blank is then cooled in the furnace.
9. The preparation method according to claim 6, characterized in that: In step (3), the cryogenic treatment involves immersing the blank in liquid nitrogen for 2 to 6 hours, then taking it out and allowing it to naturally return to room temperature. This cryogenic treatment is repeated 1 to 3 times.
10. The preparation method according to claim 9, characterized in that: In step (4), the aging process involves heating the intermediate billet from room temperature to 500-700°C under an argon atmosphere and normal pressure, holding it at that temperature for 2-5 hours, and then cooling it in the furnace.